(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: People currently reside in a smokeless tobacco -oriented society, and the threat of illicit substances is visible in every part of the world, including Pakistan. Moreover, Substance abuse has become a big problem in our society now days, therefore current study conducted on health consequences and prevalence of smokeless tobacco substance abuse among high school adolescents at taluka Qasimabad, Hyderabad, Sindh, Pakistan. Methodology: A cross sectional study conducted through predesigned survey form, in which 308 respondents were selected at random level from the full targeted sample of ninth and tenth grade pupils.. Results: the researcher revealed 22.9% of smokeless tobacco abuse among high school adolescents, in which male participants showed high prevalence as compare female. Furthermore, Areca nuts (57.1%), Safina sachet smokeless tobacco (19.2%), betel (14.6%), and Tara chewing smokeless tobacco (13.3%) had the highest percentage of smokeless tobacco used. In addition, data showed significant 0.05 association with smokeless tobacco abuse with health-related problem, i.e., throat pain, cough, mouth ulcer and headache, abdominal pain, loss of appetite and sleeping pattern disturb problem. Conclusion: It is revealed that High school adolescents abused smokeless tobacco substances and suffered worst health consequences.